Risky business: Harlem pimps’ work decisions and economic returns - Horning, Amber (Deviant behavior, 2020)
In this mixed methods study of 56 entry-level pimps in Harlem, NY, we explore how pimps’ choices to use violence or control differ by where they are selling sex, who their clientele are, and whether these violent and controlling behaviors yield higher returns. First, we qualitatively explore how pimps account for each of these choices, and how each group of choices are related to the other choices. Second, we use bivariate statistical techniques to see whether there are associations in this sample between pimps’ ages and each of those decisions, and between each of those decisions and reported earnings. We find that younger pimps work with clients and sex workers in their social networks because they are easier to hold accountable, which leads younger pimps to bypass the self-reported risks involved with more violent work, but also tends be associated with lower self-reported earnings. Older pimps gravitate toward stranger clients, which involves more risk but higher earnings. Most pimps do not describe regularly using violence either against sex workers or to protect sex workers, but the use of violence is more common among older pimps. The accounts of regularly using violence with workers are not associated with higher earnings. The idea that pimps control most aspects of how sex workers labor and other aspects of their lives such as where they live are not substantiated by the accounts of the pimps themselves, but we do find older pimps describe exerting more control over sex workers than younger pimps. We discuss the implications of our findings, which demonstrate that pimps are a diverse group who see their own violence and control decisions as related to age, location, clientele, and perceived risks and rewards.